Comparison of detection and miss rates of narrow band imaging, flexible spectral imaging chromoendoscopy and white light at screening colonoscopy: a randomised controlled back-to-back study. Issue 5 (12th July 2013) - Chung, Su Jin; Kim, Donghee; Song, Ji Hyun; Kang, Hae Yeon; Chung, Goh Eun; Choi, Jeongmin; Kim, Young Sun; Park, Min Jung; Kim, Joo Sung
Abstract : Objective: Virtual chromoendoscopy (CE) is expected to enhance adenoma yield and reduce variation in performance between colonoscopists. This study aimed to compare the efficacy of narrow band imaging (NBI), flexible spectral imaging CE (FICE) and white light (WL) colonoscopy and their impact for less experienced endoscopists. Methods: We performed a randomised tandem colonoscopy trial controlling for withdrawal time and bowel preparation. Average-risk adults undergoing screening colonoscopy were enrolled and randomly assigned to first withdrawal with one of the three imaging modalities (NBI (NBI-WL group), FICE (FICE-WL group) and WL (WL-WL group)). Eight colonoscopists were categorised into expert and non-expert subgroups. Results: 1650 subjects (mean age 51.4 years, 63.9% men) were included (550 in each group). Compared with WL, neither NBI nor FICE increased the mean number of adenomas detected per patient (0.37 vs 0.35 and 0.36; p=0.591) or the percentage of patients with adenoma (25.3% vs 24.5% and 23.6%; p=0.753). For all three modalities, expert subgroups had higher yields of adenomas than non-expert subgroups. Learning curves were observed only for non-expert subgroups with all three modalities. The percentage of missed adenomas did not differ between the three groups (20.8% by WL vs 22.9% by NBI and 26.0% by FICE, p=0.300) and was not affected by endoscopists' expertise. Conclusions: Neither NBI nor FICE improved adenoma detection or miss rates, with no difference in diagnostic efficacy between the two systems. Virtual CE had no additional benefits over WL for non-experts. Clinical trial registration number: KCT0000570.